Effect of Sodium Metabisulfite on Oxidative Stress and Lipid Peroxidation Biomarkers - Shekarforoush, Shahnaz; Ebrahimi, Parisa; Fathabad, Akbar A.; Farzanfar, Elaheh (Current Nutrition & Food Science, 2020)
Background: Sulfites are widely used as preservatives in the foods and pharmaceutical agents. It has been demonstrated that sulfites can react with a variety of cellular components and cause toxicity. Objective: The present study was designed to investigate the effects of ingested sodium metabisulfite (SMB) on serum antioxidant status in rats. Methods: Thirty-two male Wistar rats were randomly divided into control and treated groups. Treated groups received 10, 100, and 260 mg/kg body weight of SMB for 28 days. After 28 days, serum was assayed for measuring superoxide dismtase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT) activities, glutathion (GSH) level and lipid peroxidation. Results: The results showed that the activities of GPx, GR, CAT and GSH levels were significantly decreased in 100 and 260 mg/kg SMB treated rats, while malondialdehyde (MDA) level was significantly increased in 260 mg/kg treated group when compared with the control group. Conclusion: It is concluded that SMB administration as dose-dependent is associated with decreased serum antioxidant enzyme activities and increased lipid peroxidation.
Keywords: Antioxidants